ANALISIS CEMARAN MIKROBIOLOGI DAN KARAKTERISTIK KIMIA DIMSUM AYAM DI KECAMATAN WAY HALIM KOTA BANDAR LAMPUNG - Ruenda, Okti; Gidant, Raihan; Syafitri, Yosi; Lianti, Lita (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2024)
Dimsum is a popular snack made from chicken wrapped in wheat flour dough and cooked by steaming. It is favored by many due to its delicious taste and affordable price. However, dimsum sold by street vendors often lacks proper hygiene during processing and presentation, making it prone to microbial contamination. Chicken, as the main ingredient, is high in protein, which supports microbial growth. Contamination of microorganisms in food poses health risks to consumers. This study aims to analyze Total Plate Count (ALT) and Salmonella contamination and examine the correlation between chemical characteristics, such as water content and pH, and microbiological growth in chicken dimsum sold by five vendors in Way Halim District, Bandar Lampung City. The microbiological and chemical data were analyzed descriptively, and Pearson Correlation was used to determine the relationship between chemical characteristics and microbial growth. The results showed that all chicken dimsum samples exceeded the maximum ALT limit, and two samples tested positive for Salmonella. Referring to SNI 7756:2013, the standard for siomay quality and safety is a maximum ALT of 5×104 CFU/g and negative/25 g for Salmonella. The correlation test indicated that water content and pH had a significant relationship with ALT growth. The chicken dimsum sample with the highest ALT was the DC sample (6.31 log CFU/g), while the lowest was the DA sample (5.35 log CFU/g). Salmonella contamination was found in the DC and DE samples.